2020
DOI: 10.4149/neo_2020_190731n696
|View full text |Cite
|
Sign up to set email alerts
|

miR-326 inhibits the progression of papillary thyroid carcinoma by targeting MAPK1 and ERBB4

Abstract: Papillary thyroid carcinoma (PTC) is the prevalent histotype of thyroid cancer, with increasing incidence worldwide. MicroRNAs (miRNAs) could play an important role in the development and progression of human cancers. Interestingly, miR-326 was validated as one of the downregulated miRNAs in PTC. Therefore, it is necessary to research the function of miR-326 involved in the progression of PTC. In the current study, we detected the downregulation of miR-326 in PTC tissues and cell lines. The miR-326 overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
(24 reference statements)
2
14
0
Order By: Relevance
“…Some miRNAs are also involved in immune regulation [ 36 , 37 ]. MiR-326 is involved in the progress of various tumors, including lung cancer, and acts as an inhibitory factor [ 21 , 38 , 39 ]. However, the regulatory effect of miR-326 on immune checkpoint has been rarely explored.…”
Section: Discussionmentioning
confidence: 99%
“…Some miRNAs are also involved in immune regulation [ 36 , 37 ]. MiR-326 is involved in the progress of various tumors, including lung cancer, and acts as an inhibitory factor [ 21 , 38 , 39 ]. However, the regulatory effect of miR-326 on immune checkpoint has been rarely explored.…”
Section: Discussionmentioning
confidence: 99%
“…12 MiR-326 has been revealed to take part in embryonic development, oncogenesis, chemotherapy resistance, immunomodulation, and cell invasion. 13 MiR-326 has also been identified as a tumor suppressor in a range of tumors, such as papillary thyroid cancer 14 and oral squamous cell cancer, 15 as well as being associated with BC development. However, the mechanism by which miR-326 modulates the advancement of BC has so far not been clearly explained.…”
Section: Introductionmentioning
confidence: 99%
“…miR-193a-5p directly targets SPOCK1 in hepatocellular carcinoma to repress its malignancy (39). Additionally, miR-330-5p and miR-326 have both been demonstrated to play tumor-suppressive roles in PTC progression (20,21). However, research on miR-193a-5p in PTC is limited.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that miR-330-5p mediates the positive regulation of long intergenic non-protein-coding RNA 003311 on cancer stem-like features in PTC (20). miR-326 suppresses PTC cell proliferation and metastasis by inhibiting MAPK1 and erb-b2 receptor tyrosine kinase (ERBB) 4 (21).…”
Section: Introductionmentioning
confidence: 99%